A Framework for Supporting the Selection of a Food Packing System - Oddershede-Herrera, A; Palominos-Belmar, P; Quezada-Valenzuela, F (Springer Nature, 2023)
The aim of the study is to provide a methodological tool for those involved in the process of implementing packing systems in the food industry. A model is constructed, based on empirical data and expert judgments, to evaluate different packing systems for food products. The design involves the analysis of the problem situation from different perspectives to support the selection of an alternative, recognizing the critical factors involved. Taking into account that, from a marketing perspective, the packing must be attractive in all senses, qualitative aspects are introduced together with the technical ones. The study takes into consideration technical requirements related to the transport of food products from their manufacturing system to the final consumer. By using a multicriteria approach, it is possible to incorporate quantifiable and intangible factors and to deal with conflicting objectives. Through a case study, a decision model is presented to define and evaluate alternative packing systems, providing an analytic method for deciding the most appropriate system in a food production plant. © The Editor(s) (if applicable) and The Author(s), under exclusive license to Springer Nature Switzerland AG 2023.
Keywords: Decision model; Evaluation process; Food packing system